Библиотекарь: роман / Михаил Елизаров - Елизаров Михаил (Ад Маргинем, 2007)
Экземпляры: ООВ (20131018) / Инвентарный номер: 33446 / Цена: 234.08 / Сис.шифр: 84(2Рос) / Авт.знак: Е 51 / ГРНТИ: 17 / ББК: 84(2Рос)